Simplified probabilistic seismic performance assessment of plan-asymmetric buildings. - Dol?ek, Matja? (Earthquake engineering & structural dynamics.)
A relatively simple approach for the probabilistic seismic performance assessment of plan-asymmetric structures has been proposed. It is based on the PEER probabilistic framework, in which the most demanding part, i.e. the incremental dynamic analysis (IDA), is replaced by the much simpler Incremental N2 (IN2) analysis. Predetermined default values for dispersion measures are needed for the practical implementation of this approach, which can be used for the analysis of plan-asymmetric buildings requiring a 3D structural model. In this paper, this simplified approach is summarized. Its application is demonstrated by means of an example of a three-storey reinforced concrete frame (SPEAR) building. The results are compared with the results of a more accurate approach, based on IDA. The test example demonstrates the viability of the proposed approach.